Advances in the science and technology of insulin delivery: A review - Emmanuel O. Olorunsola, Mfonobong F. Alozie, Koofreh G. Davies, Musiliu O. Adedokun (Journal of Applied Pharmaceutical Science, 2021)
Insulin, which was discovered in 1921, is the cornerstone of the management of diabetes mellitus (DM), and for many years, it was sourced from porcine and bovine pancreas and administered by parenteral injection. This study aimed to review the various advances in the science and technology of the delivery of this golden agent. It was found that the drug which was initially obtained from the pancreas of pigs and cows is now available in the human forms by modification of the animal versions or by recombinant technology. Insulin analogues have equally been produced. Beta cells, pancreatic and genetically engineered non-beta-cells transplantation as well as artificial pancreas have also been employed for insulin delivery. The parenteral administration, which is characterized by a tremendous life expectancy, was found to have evolved from the use of insulin syringe and needle (with limitation of pains at injection site) to the use of pen, jet, and pump. Further advances have produced integrated sensor-augmented pump therapy and cloud-based data systems, with the sensor-augmented pumps offering blood glucose monitoring and insulin delivery, while the cloud-based data systems enable the transmission and storage of the patient data obtained from glucose monitoring and insulin dosing. The non-invasive methods of administration that have been researched are intranasal, pulmonary, transdermal, and oral routes, utilizing various technologies. Conclusively, the science and technology of insulin delivery has witnessed a lot of advances, and different researches and clinical trials are ongoing toward obtaining more effective formulations and delivery.
Keywords: Delivery, device, diabetes mellitus, injection, insulin, pancreas